2002
DOI: 10.1002/1522-2683(200202)23:3<367::aid-elps367>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis of anionic analytes in methanol: Effect of counter-ions on electrophoretic mobility

Abstract: Mobilities of 11 substituted benzoates and 3 nitrophenolates were determined in non-aqueous methanol with Li+, Na+, K+, Rb+, and tetrabutylammonium (Bu4N+) as counter-ions of the background electrolyte. The influence of the ionic concentration of the background electrolyte on the mobility of the analyte anions is more pronounced compared to aqueous solutions. The deviation from the dependence of the mobilities on the ionic strength from the Debye-Hückel-Onsager theory indicates the occurrence of ion-pair forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…However, ion-pair formation seems to be more pronounced in MeOH than in ACN. Porras et al [47] have also demonstrated that the effect of BGE counterions (alkali metal ions and tetrabutylammonium ion) on the mobilities of eleven substituted benzoates and three nitrophenolates depends, as predicted by the theory, on the size of the solvated counterion.…”
Section: Theoretical Aspectsmentioning
confidence: 88%
“…However, ion-pair formation seems to be more pronounced in MeOH than in ACN. Porras et al [47] have also demonstrated that the effect of BGE counterions (alkali metal ions and tetrabutylammonium ion) on the mobilities of eleven substituted benzoates and three nitrophenolates depends, as predicted by the theory, on the size of the solvated counterion.…”
Section: Theoretical Aspectsmentioning
confidence: 88%
“…As the analyte ion has typically a much lower concentration than the BGE ions, pairing does not affect the pH or ionic strength of the BGE to a considerable extent, but it clearly affects the mobility of the analyte ion. In addition, if different BGE counter ions are applied the mobility of the analyte ion may vary depending on the strength of ion-pair formation with the counter ion [54,60]. It should be mentioned that in Fig.…”
Section: Methanol As Solventmentioning
confidence: 99%
“…where m is the mobility of the polyion at finite ionic strength (in units of 10 ÿ4 cm 2 V ÿ1 s ÿ1 ) and m o is the mobility at zero ionic strength (Li et al, 1999;Porras et al, 2002).…”
Section: Henry Equationmentioning
confidence: 99%